Transapical mitral valve repair procedures: Primetime for microinvasive mitral valve surgery. Issue 12 (22nd September 2021) - D'Onofrio, Augusto; Fiocco, Alessandro; Nadali, Matteo; Gerosa, Gino
Abstract: Introduction: Nowadays micro‐invasive‐procedures (off‐pump, beating‐heart) for mitral valve repair (MVRe) are abruptly expanding with the potential to be adopted as a valuable alternative to surgery. In the present manuscript, the authors review the available technologies intended to treat mitral regurgitation (MR) through transapical approach, including annuloplasty and chordal‐repair options. Annuloplasty: To date, Valcare Amend is the only transapical MV ring to have been implanted in patients. The device allows for stabilization of the annulus through a complete semirigid d ‐shaped ring. The first‐in‐human successful procedure was performed in 2016 by our Group and subsequent clinical experience included a total of 14 implanted patients. Currently, the technology is under clinical trial evaluation to validate the efficacy and safety profile of the device. Chordal Repair: Beating‐heart chordal implantation via transapical approach is a current feasible, safe and reproducible option. Neochord DS1000 is the most widely used technology in the field, with a solid procedural experience and good results in well‐selected patients. Its clinical use has been validated in Europe since 2012, while it is still under clinical investigation in the United States. Harpoon MVRe system is a novel technology, recently CE‐mark approved for clinical use. Discussion and Conclusions: Transapical micro‐invasive technologies are current viable therapies to treat MR in selected patients. Although there are still several limitations that preclude an extensive use of such procedures, their results are promising in well‐selected patients. Embracing transcatheter MVRe therapies should guide the cardiac surgeon through the new revolution of micro‐invasive MV tailored repair.